Mosaic Bovine Viral Diarrhea Virus Antigens Elicit Cross-Protective Immunity in Calves - Sangewar, Neha; Hassan, Wisam; Lokhandwala, Shehnaz; Bray, Jocelyn; Reith, Rachel; Markland, Mary; Sang, Huldah; Yao, Jianxiu; Fritz, Bailey; Waghela, Suryakant D.; Abdelsalam, Karim W.; Chase, Christopher C. L.; et al. (Frontiers in Immunology, 2020)
Bovine Viral Diarrhea Virus (BVDV) is an important pathogen that plays a significant role in initiating Bovine Respiratory Disease Complex (BRDC) in cattle. The disease causes multi-billion dollar losses globally due to high calf mortality and increased morbidity leading to heavy use of antibiotics. Current commercial vaccines provide limited cross-protection with several drawbacks such as safety, immunosuppression, potential reversion to virulence, and induction of neonatal pancytopenia. This study evaluates two prototype vaccines containing multiple rationally designed recombinant mosaic BVDV antigens for their potential to confer cross-protection against diverse BVDV strains. Genes encoding three novel mosaic antigens, designated E2123, NS2-31, and NS2-32, were designed in silico and expressed in mammalian cells for the formulation of a prototype protein-based vaccine. The mosaic antigens contain highly conserved protective epitopes from BVDV-1a, -1b, and -2, and included unique neutralizing epitopes from disparate strains to broaden coverage. We tested immunogenicity and protective efficacy of Expi293TM-expressed mosaic antigens (293F-E2123, 293F-NS2-31, and 293F-NS2-32), and baculovirus-expressed E2123 (Bac-E2123) mosaic antigen in calves. The Expi293TM-expressed antigen cocktail induced robust BVDV-specific cross-reactive IFN-γ responses, broadly neutralizing antibodies, and following challenge with a BVDV-1b strain, the calves had significantly (p < 0.05) reduced viremia and clinical BVD disease compared to the calves vaccinated with a commercial killed vaccine. The Bac-E2123 antigen was not as effective as the Expi293TM-expressed antigen cocktail, but it protected calves from BVD disease better than the commercial killed vaccine. The findings support feasibility for development of a broadly protective subunit BVDV vaccine for safe and effective management of BRD.